Uses Of Lime -Rice Husk Ash And Plastic Fibers As Mixtures-Material In High-Plasticity Clayey Subgrade: A Preliminary Study - Muhammad, Ario; Muntohar, Agus Setyo (Jurnal Semesta Teknika, 2007)
Silica produced from rice husk ashes have investigated successfully as a pozzolanic material in soil stabilization. However, rice husk ash cannot be used solely since the materials lack in calcium element. As a result, rice husk ash shall be mixed with other cementitious materials such as lime and cement to have a solid chemical reaction in stabilization process. The main objective of this study focused on bearing capacity of the stabilized clayey subgrade with lime-rice husk ash and fibers. The main laboratory test shall be compaction and CBR tests. The investigation results revealed that the inclusion of lime-rice husk ash-fiber into the soil decreased MDD and OMC. On the other hand, stabilization and reinforcement with lime-rice husk ash and fibers waste improved significantly the CBR valuesÂ